2021
DOI: 10.1177/03000605211010073
|View full text |Cite
|
Sign up to set email alerts
|

Refractory pleural effusion as a rare complication of pulmonary vascular stenosis induced by fibrosing mediastinitis: a case report and literature review

Abstract: Fibrosing mediastinitis (FM) is a progressive, life-threatening disease characterized by extrinsic compression of mediastinal bronchovascular structures, and the clinical manifestations largely depend upon the affected structures. Pleural effusion is rarely reported in patients with FM. We herein describe a 70-year-old man who presented with recurrent breathlessness and refractory left pleural effusion. He was misdiagnosed with and treated for tuberculous pleurisy for several months. Thoracentesis revealed a t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 35 publications
1
6
0
Order By: Relevance
“…When a CEH develops in the mediastinum, compression of the right ventricle causes RVOT stenosis, resulting in an elevated RVP. In addition, PH may also occur due to external compression of the pulmonary artery; PH due to compression of the pulmonary artery and vein by fibrotic mediastinitis has been previously reported (10). Intrathoracic CEHs are known to cause tracheal and oesophageal compression and consequent aspiration pneumonia (11) and oesophageal transit obstruction (12).…”
Section: Discussionmentioning
confidence: 99%
“…When a CEH develops in the mediastinum, compression of the right ventricle causes RVOT stenosis, resulting in an elevated RVP. In addition, PH may also occur due to external compression of the pulmonary artery; PH due to compression of the pulmonary artery and vein by fibrotic mediastinitis has been previously reported (10). Intrathoracic CEHs are known to cause tracheal and oesophageal compression and consequent aspiration pneumonia (11) and oesophageal transit obstruction (12).…”
Section: Discussionmentioning
confidence: 99%
“…However, among the 36 patients with PH-FM recruited in this study, 31 (86%) had pleural effusions and 19 (53%) were bilaterally afflicted, which agrees to the notion that the pleural effusion in the PH-FM patients was mainly caused by pulmonary vein stenosis (PVS). 9 , 21 Indeed, among the 30 patients with FM-caused PVS recruited in our prior study, 19 suffered from refractory pleural effusion; Furthermore, 17 out of the 19 patients with refractory pleural effusion were relieved by pulmonary vein angioplasty. 21 Admittedly, the PH-induced RHF is also involved to varying extents in the formation of pleural effusion in the patients with PH-FM.…”
Section: Discussionmentioning
confidence: 99%
“…6,7 The protruding proliferative fibrotic tissues compress or encroach on the mediastinal structures, including bronchus, esophagus, vena cava, and pulmonary vasculature, leading to atelectasis, superior vena cava syndrome (SVCS), PH, and pleural effusion. 8,9 Chest X-ray radiography (CXR) is an inexpensive and convenient examination approach for PH with availability and accessibility in conventional clinical settings. 10 Previous study indicated that CXR features, including FM dyad (prominent main pulmonary artery and atelectasis) and FM triad (the dyad plus refractory pleural effusion), are important diagnostic clues for PH-FM.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although no publications clearly demonstrate the association between pulmonary artery stenosis/atresia and refractory pleural effusion, there are several case reports for adults in the literature. One of them is a refractory pleural effusion that developed on the left hemithorax as a result of pulmonary artery stenosis due to fibrosing mediastinitis in a 70-year-old man (16). However, there is no case involving this situation in the neonatal and infant age group.…”
Section: Discussionmentioning
confidence: 99%